Selective entrainment of the Drosophila circadian clock to daily gradients in environmental temperature - Currie, Jake (BioMed Central, 2009)
BACKGROUND: Circadian clocks are internal daily time keeping mechanisms that allow organisms to anticipate daily changes in their environment and to organize their behavior and physiology in a coherent schedule. Although circadian clocks use temperature compensation mechanisms to maintain the same pace over a range of temperatures, they are also capable of synchronizing to daily temperature cycles. This study identifies key properties of this process. RESULTS: Gradually ramping daily temperature cycles are shown here to synchronize behavioral and molecular daily rhythms in Drosophila with a remarkable efficiency. Entrainment to daily temperature gradients of amplitudes as low as 4°C persisted even in the context of environmental profiles that also included continuous gradual increases or decreases in absolute temperature. To determine which elements of daily temperature gradients acted as the key determinants of circadian activity phase, comparative analyses of daily temperature gradients with different wave forms were performed. The phases of ascending and descending temperature acted together as key determinants of entrained circadian phase. In addition, circadian phase was found to be modulated by the relative temperature of release into free running conditions. Release at or close to the trough temperature of entrainment consistently resulted in phase advances. Re-entrainment to daily temperature gradients after large phase shifts occurred relatively slowly and required several cycles, allowing flies to selectively respond to periodic rather than anecdotal signals. The temperature-entrained phase relationship between clock gene expression rhythms and locomotor activity rhythms strongly resembled that previously observed for light entrainment. Moreover, daily temperature gradient and light/dark entrainment reinforced each other if the phases of ascending and descending temperature were in their natural alignment with the light and dark phases, respectively. CONCLUSION: The present study systematically examined the entrainment of clock-controlled behavior to daily environmental temperature gradients. As a result, a number of key properties of circadian temperature entrainment were identified. Collectively, these properties represent a circadian temperature entrainment mechanism that is optimized in its ability to detect the time-of-day information encoded in natural environmental temperature profiles. The molecular events synchronized to the daily phases of ascending and descending temperature are expected to play an important role in the mechanism of circadian entrainment to daily temperature cycles.